2021
DOI: 10.47162/rjme.62.3.21
|View full text |Cite
|
Sign up to set email alerts
|

The procoagulant status. Hypercoagulability as a risk factor of primary and secondary infertility

Abstract: Thrombophilia is a disorder that makes patients susceptible to intravascular thrombosis that may increase the risk of developing a pregnancy on a known pathology. The female patient diagnosed with hypoplastic uterus and hereditary thrombophilia had a favorable evolution under properly administered anticoagulant treatment. The homozygous status for the C677T mutation may lead to an increase in plasma homocysteine levels, especially in pregnant women, being an associated risk factor for thrombosis. The risk of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In terms of age, we selected patients between 20 and 35 years old to avoid being associated with placental changes caused by chronic pathologies, common at advanced ages [ 40 , 41 , 42 , 43 , 44 , 45 ]. However, between the two groups (C+ and C-), we noticed that the average age of the patients in the C+ group was approximately four years lower compared to the C- group.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of age, we selected patients between 20 and 35 years old to avoid being associated with placental changes caused by chronic pathologies, common at advanced ages [ 40 , 41 , 42 , 43 , 44 , 45 ]. However, between the two groups (C+ and C-), we noticed that the average age of the patients in the C+ group was approximately four years lower compared to the C- group.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the reduction of PGP9.5 and S100 in the mucosal and muscular layers of the FTs suggests that injury to the nerve fibers in the ampulla tissue may negatively impact on the release of transmitters including acetylcholine (ACh), adrenaline, noradrenaline, and the modulation of the nerve reflex. These events may reduce oviduct motility by influencing the vascular muscle contractility, the tubal smooth muscle, ciliary beat activity and the secretory processes of the mucosal epithelial cells [3], thus resulting in the pathogenesis of FP.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive suction or curettage can also readily cause damage to the nerves between the endometrium and the myometrium. In a previous study, Neamtu et al [3] suggested that the motility of the FTs was influenced by both nerves and hormones. Several neuropeptides, such as neuropeptide Y-immunoreactivity (NPY), have been de-tected in nerve fibers in the FTs [4].…”
Section: Introductionmentioning
confidence: 97%
“…Inherited thrombophilia comprises conditions in which a genetic mutation affects the amount or the function of a protein in the coagulation pathway. Mutations in several genes have been shown to be involved: G1619A (factor V Leiden), R2 H1299R (factor V Leiden polymorphism), A1298C (methylenetetrahydrofolate reductase (MTHFR) enzyme mutation), C677T (MTHFR polymorphism), V34L (factor XIII polymorphism), G20210A (mutation of the prothrombin gene), a/b L33P (ribosomal polymorphism of MTHFR enzyme), and 4G / 5G (plasminogen activator inhibitor-1 (PAI-1)) ( Neamţu et al , 2021 ).…”
Section: Investigations For Rifmentioning
confidence: 99%
“…Inherited thrombophilia has been implicated in early pregnancy loss and implantation failure, by impairment of the vascular changes necessary for successful pregnancy ( Qublan et al , 2006 ; Neamţu et al , 2021 ).…”
Section: Investigations For Rifmentioning
confidence: 99%